PENGARUH KOMPETENSI, KEPEMIMPINAN, DISIPLIN, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Kantor Dinas Tenaga Kerja Transmigrasi dan Kependudukan Provinsi Jawa Tengah) (Students' Journal of Economic and Management, 2015)
The Purpose of this reseach was to determine the effect of competence, leadership, discipline, and compensation, jointly or partially on employee performance. The data used in this study is primary data, with the questionnaire as a research instrument, which is then processed by calculation SPSS (Statistical Product and Solutions) version 19. The population in this study are employees of the Office of Manpower and Transmigration and Population of Central Java Province, which totaling 416 employees. The sampling technique in this research using random sampling using Slovin formula, so the respondents amounted to 81 respondents. The analytical tool used is multiple linear regression. The results showed that there was a significant positive effect on employee performance between competence. There was a significant positive effect between leadership on employee performance. There was a significant positive effect on employee performance between disciplines. There was a significant positive effect between compensation on employee performance. Keywords: Competence, leadership, discipline, compensation, and employee performance